2021
DOI: 10.1097/hs9.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Has Time-dependent On- and Off-target Effects on Plasma Biomarkers and Immune Cells in Chronic Lymphocytic Leukemia

Abstract: Ibrutinib is a covalently binding inhibitor of the B-cell receptor signaling-mediator Bruton's tyrosine kinase (BTK) with great efficacy in chronic lymphocytic leukemia (CLL). Common side effects like atrial fibrillation (AF), bleeding and infections might be caused by ibrutinib's inhibition of other kinases in non-B cells. Five-year follow-up of plasma biomarkers by proximity extension assay and immune cell numbers by flow cytometry during ibrutinib treatment revealed that 86 of the 265 investigated plasma bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
0
17
1
Order By: Relevance
“…Patients with chronic lymphocytic leukemia (CLL) have an increased risk of severe infections due to disease- and treatment-related immunodeficiency [ 1 , 2 ] that does not exclude novel precision therapeutics such as ibrutinib [ 3 , 4 ]. Two early international surveys reported that hospital-admitted Covid-19 patients with CLL had a high fatality rate [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic lymphocytic leukemia (CLL) have an increased risk of severe infections due to disease- and treatment-related immunodeficiency [ 1 , 2 ] that does not exclude novel precision therapeutics such as ibrutinib [ 3 , 4 ]. Two early international surveys reported that hospital-admitted Covid-19 patients with CLL had a high fatality rate [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proliferating T cells and expression of activation markers and immune checkpoints (PD-1, CTLA-4) also decreased both after treatment with ibrutinib ( 64 , 65 , 69 ), acalabrutinib ( 68 ) and zanubrutinib ( 53 ), also likely reflecting the decrease in tumor burden.…”
Section: Immunomodulatory Effects Of Btk Inhibitorsmentioning
confidence: 93%
“…The effects of ibrutinib on the T-cell compartment have been reviewed by Mhibik et al (63). Even if the findings regarding the changes in T-cell numbers, including major subsets, during ibrutinib treatment have been controversial, with both reports on decrease (64,65) and increase (66), the available evidence seems to point out that T cells decrease in parallel with the reduction of the tumor burden (64,65,67). Indeed, T cells are usually abnormally elevated in R/R CLL patients (61), chronically activated by tumor antigens.…”
Section: Effects On Adaptive Immunitymentioning
confidence: 99%
“…Sequence alignment of BTK and Src family kinases and screening of first-generation inhibitors that bind to the ATP-site revealed that C481 in BTK could act as a nucleophile and form a covalent bond with an inhibitor ( 30 ). This led to the birth of ibrutinib, the first irreversible BTK inhibitor, which is approved as treatment for several B-cell malignancies ( 25 , 31 ).…”
Section: Btk Inhibitorsmentioning
confidence: 99%